2021
DOI: 10.1097/sla.0000000000005044
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Hospital Volume and Failure to Rescue After Open or Endovascular Repair of Intact Abdominal Aortic Aneurysms in the VASCUNET and International Consortium of Vascular Registries

Abstract: Objective: To investigate the association between hospital volume and failure to rescue (FtR), after open repair (OAR), and endovascular repair (EVAR) of intact abdominal aortic aneurysms (AAA) among centers participating in the VASCUNET and International Consortium of Vascular Registries. Summary of Background Data: FtR (ie, in-hospital death following major complications) is a composite end-point representing the inability to treat complications effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 38 publications
0
9
0
2
Order By: Relevance
“…It is described that in intact AAA-repairs, an increase in hospital volume is significantly associated with less failure to rescue, which could be caused due to prompt recognition and management of complications in large volume hospitals. 31 Spinal cord ischemia as well as cerebral embolism are the most feared complications following management of thoracic aortic aneurysms 15 and complex aortic aneurysms. 37 Previous studies have reported paraplegia rates of 4.1% and 5.2% following FEVAR and BEVAR, 27,37 which is in accordance with our present results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is described that in intact AAA-repairs, an increase in hospital volume is significantly associated with less failure to rescue, which could be caused due to prompt recognition and management of complications in large volume hospitals. 31 Spinal cord ischemia as well as cerebral embolism are the most feared complications following management of thoracic aortic aneurysms 15 and complex aortic aneurysms. 37 Previous studies have reported paraplegia rates of 4.1% and 5.2% following FEVAR and BEVAR, 27,37 which is in accordance with our present results.…”
Section: Discussionmentioning
confidence: 99%
“…It is described that in intact AAA-repairs, an increase in hospital volume is significantly associated with less failure to rescue, which could be caused due to prompt recognition and management of complications in large volume hospitals. 31…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Dutch analysis also showed a significant effect of hospital volume on perioperative mortality following complex EVAR, with high volume centers demonstrating decreased mortality rates [ 30 ]. D’Oria et al investigated the association between hospital volume and failure to rescue after EVAR and open aortic repair of intact abdominal aortic aneurysms and found a significant association: hospitals in the top volume quartiles achieve the lowest mortality after a complication has occurred [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the concept of failure to rescue (which is a composite endpoint defined as peri-operative death after experiencing at least one major complication) has emerged as an additional and more sensitive marker for team quality assessment in aortic interventions. Future research may also be directed toward better understanding of failure to rescue after complex endovascular aortic repair, as this remains relatively unaddressed in the available literature [ 31 ].…”
Section: Frequency and Impact Of Post-operative Complications After F...mentioning
confidence: 99%